إعجاز القرآن الكريم وتفسيره بين الاتجاه العلمي وأسلمة المعرفة - مخلوف حسام الدين (مجلس رئاسة الوزراء طرابلس-ليبيا, 2024)
إنَّ القرآن الكريم حافل بالإشارات العلمية التي تعتبر شكلًا من أشكال التحدّي الذي بلَّغه النبيُّ الأميُّ صلَّى الله عليه وسلَّم عن ربِّ العزَّة والجلال، فهو يحوي من حقائق هذا الكون ما لم يستطع العلم إدراكه إلا مؤخرًا، وإذا ما وافقت الحقائق العلمية الحديثة صارت إعجازًا يشهد على صحَّة مصدريَّة القرآن العظيم ونبوَّة رسوله الكريم، وعلى الرَّغم من أنَّ الوحي القرآني المعجز من أهم مصادر المعرفة التي عرفها الإنسان -لتطرّقه لمختلف أبواب العلوم- غير أنه لم ينل حظه من الانطلاق منه في إنتاج العلم التجريبي وتحقيق المنهج العلمي من المنظور القرآني ابتداءً، في حين أنَّ جهود العلماء في الكشف عن التطابق والتوافق والتكامل بين علوم العصر الحديث وإشارات القرآن الكريم لا تزال جاريةً ومتتابعةً كلَّما استجدَّت النظريَّات وتحقَّقت، ومن هنا جاءت هذه الدراسة التأصيلية التحليلية لتحاول إبراز مصادر المعرفة ومنهجيتها بنظرة إسلامية متكاملة، ولترصد الاختلاف الجوهريّ بين التفسير العلميّ للقرآن الكريم وإعجازه العلميّ، فالتفسيرُ العلميُّ هو استخدام مكتشفات العلم التجريبيّ في بيان معاني الآيات القرآنية ودلالاتها، في حين أنَّ الإعجاز العلميّ هو استخدام مخرجات التفسير العلميّ ونتائجه في إثبات صدق النُّبوَّة وصحَّة مصدريَّة القرآن الكريم، وقد تمَّ ذلك من خلال مبحثين، تناول المبحث الأول الإطار النظريّ للدراسة والمتمثّل في مصادر المعرفة ومنهجيّتها، وجاء في المبحث الثاني تفصيل مسألة الإعجاز العلميّ وضوابطه، والتفسير العلميّ للقرآن الكريم وأسسه، واختتمت الدراسة بذكر أهم النتائج والتوصيات. Abstract: The Holy Quran is full of scientific references that are considered a form of challenge that the illiterate Prophet, may God bless him and grant him peace, conveyed from the Lord of Glory and Majesty. It contains facts of this universe that science has not been able to comprehend until recently. If they agree with modern scientific facts, they become a miracle that testifies to the authenticity of the source of the Great Quran and the prophethood of its noble Messenger. Despite the fact that the miraculous Quranic revelation is one of the most important sources of knowledge known to man - due to its coverage of various branches of science - it has not received its share of starting from it in producing experimental science and achieving the scientific method from the Quranic perspective from the beginning, while the efforts of scientists to discover the compatibility, agreement and integration between the sciences of the modern era and the references of the Holy Quran are still ongoing and continuous whenever theories emerge and are realized. Hence, this original analytical study came to try to highlight the sources of knowledge and its methodology with an integrated Islamic perspective, and to monitor the fundamental difference between the scientific interpretation of the Holy Quran And its scientific miracle, as scientific interpretation is the use of the discoveries of experimental science in explaining the meanings and implications of the Qur’anic verses, while the scientific miracle is the use of the outputs of scientific interpretation and its results in proving the truth of prophecy and the validity of the source of the Holy Qur’an, and this was done through two chapters, the first chapter dealt with the theoretical framework of the study represented in the sources of knowledge and its methodology, and the second chapter came in detail the issue of scientific miracle and its controls, and the scientific interpretation of the Holy Qur’an and its foundations, and the study concluded by mentioning the most important results and recommendations.
Intervention
Keywords: القرآن; الإعجاز; التفسير; لعلم; أسلمة المعرفة